AS-Router: A novel allocation service for efficient Network-on-Chip - Katta, Monika (Elsevier, 2025)
Assigning input ports to output ports and allowing flits to pass through the switch without colliding is accomplished by Switch Allocation (SA), a crucial pipeline stage in the Network-on-Chip (NoC) router. Earlier research improved the efficiency of matching to enhance SA processes. The studies in question, however, failed to account for the importance of information sharing between the various phases of the router’s pipeline. To improve NoC routers’ allocation, this article introduces the Allocation Service (AS) concept. By adding a new pipeline stage called Request Finalization (RF) before the SA stage, the AS can be optimized. The RF stage’s objective is to complete the uniform request and Endpoint Congestion Causing (EPC) requests for SA before sending them on their way. These results inform the proposal of a new design, the CUE-Router, to increase AS by the integration of an RF stage and inter-pipeline communication between routers. Two new types of router architecture form the basis for CUE-Router. The first thing we do in this work is introduce URR-Router, a router that only allocates EPC requests if there are no uniform requests in the SA stage, effectively giving uniform requests a priority. The second example is the EPR-Router, which alleviates endpoint congestion by favoring EPC requests over uniform ones. In this work, we take a fresh look at the SA process optimization that underpins the low-latency CUE-Router architecture by cycling through a series of prioritization changes between uniform requests and EPC requests. CUE-Router greatly improves SA efficiency and network performance by facilitating communication between the various stages of the pipeline. Based on the results of the analysis, our approach has the potential to significantly enhance performance with minimal additional effort.